2014
DOI: 10.1016/j.ijsu.2014.08.373
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative and postoperative outcomes of perforated diverticulitis Hinchey II and III: Open Hartmann's procedure vs. laparoscopic lavage and drainage in the elderly

Abstract: Hartmann's procedure (HP) is the most performed technique for acute diverticulitis. Laparoscopic lavage and drainage (LLD) is an option evaluated as definitive treatment for diverticulitis Hinchey grade II-III. Aim of the study is to analyze and compare LLD vs HP outcomes. From January 1st 2009 and December 31st 2012 we prospectively enrolled 30 patients with diagnosis of acute diverticulitis Hinchey grade II-III. Fourteen patients underwent to LLD (LLD group, LLDG) and 16 patients to HP (Hartmann group, HG). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 24 publications
0
14
0
5
Order By: Relevance
“…White et al [16] concluded that peritoneal lavage is preferable in patients with a Hinchey class 3 perforation, and Gentile et al [25] demonstrated that peritoneal lavage offers several advantages, including decreased need for ICU admission and shorter length of stay when compared to the Hartmann's procedure in Hinchey class 2 and 3 perforations, but both studies have a relatively small group of patients , and the latter includes the Hinchey class 2 patients, who could also be treated with percutaneous drainage alone. The meta-analysis conducted by Cirocchi et al [23] concluded that further investigation is needed to determine the role of peritoneal lavage when compared with primary anastomosis and the Hartmann's procedure in Hinchey class 3 and 4 perforations.…”
Section: Discussionmentioning
confidence: 99%
“…White et al [16] concluded that peritoneal lavage is preferable in patients with a Hinchey class 3 perforation, and Gentile et al [25] demonstrated that peritoneal lavage offers several advantages, including decreased need for ICU admission and shorter length of stay when compared to the Hartmann's procedure in Hinchey class 2 and 3 perforations, but both studies have a relatively small group of patients , and the latter includes the Hinchey class 2 patients, who could also be treated with percutaneous drainage alone. The meta-analysis conducted by Cirocchi et al [23] concluded that further investigation is needed to determine the role of peritoneal lavage when compared with primary anastomosis and the Hartmann's procedure in Hinchey class 3 and 4 perforations.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of publication bias was indicated by the data points forming a symmetric funnel-shaped distribution (funnel plot), and a 1-tailed significance level of p > 0.05 (Egger's test) [15] . Publication bias was only assessed if there were >10 studies [16] . All analyses were performed using comprehensive metaanalysis statistical software, version 2.0 (Biostat, Englewood, N.J., USA).…”
Section: Data Extraction and Analysismentioning
confidence: 99%
“…Преимущества операций с формированием первичного толстокишечного анастомоза, по сравнению с ОГ, заключаются в лучшем качестве жизни, меньшей частоте раневых осложнений, более щадящем втором этапе хирургического лечения, при равных либо меньших показателях осложнений и летальности [2,25,35,46] [25,29,50], а выбор в пользу операций с формированием первичного анастомоза предлагают решать строго индивидуально, на основе комплекса факторов: степени тяжести перитонита и абдоминального сепсиса (АС), состояния остальных отделов ОК, стадии кишечной недостаточности, возраста, степени декомпенсации сопутствующих заболеваний, что с учетом всех условий бывает не выполнимо более чем у ¼ пациентов [17,29,50]. Другим направлением научного поиска при решении проблемы перитонита дивертикулярного генеза, является применение лапароскопической санации без выполнения первичной резекции ОК, что гипотетически создает условия для одноэтапного хирургического лечения после купирования гнойного воспаления в брюшной полости [6,11,18,40,48]. За рубежом накоплен определенный позитивный опыт использования нерезекционного подхода в лечении перфоративного дивертикулита [38,40,50,51].…”
unclassified
“…К более однозначным выводам пришли Gentile V. и соавт. [18], выявившие достоверные преимущества лапароскопической санации перед ОГ при стадиях II-III по Hinchey E.J., выразившиеся в сокращении времени операции, темпов восстановления функции кишечника, необходимости нахождения в реанимационном отделении в ран-ней активизации и меньшей продолжительности госпитализации. Хотя к очевидному недостатку такого рода исследований, отмечаемому самими авторами, относится невозможность определить степень тяжести перитонита и АС, нельзя не признать право на существование точки зрения, что выполнение лапароскопической санации имеет преимущества не только при отсутствии распространенного перитонита у пациентов, с выраженными сопутствующими заболеваниями, выполнение открытой операции которым крайне рискованно [38,40,50,51], но и при гораздо более тяжелых формах внутрибрюшной инфекции [48].…”
unclassified